Von Sprache zu Sprache: Winkler Translating Rübner Translating Himself - Ben-Horin, Michal (Naharaim, 2025)
In his 1957 Hebrew language poetry collection, Ha'esh ba'even (The Fire in the Stone), Tuvia Rübner included a poem dedicated to his sister who was murdered in Auschwitz. A close reading of this poem shows its strong connection to German poems he published in various collections during the 1990s, some of which were written shortly after he immigrated to Mandatory Palestine from Bratislava in 1941. Such dwelling between languages comes to the fore in Manfred Winkler's German translation of Rübner's Hebrew poem. Focusing on this poem, while employing theories from translation and memory studies, this article examines the relationship between literary self-translation and the working-through of trauma. I argue that the oscillation between German and Hebrew encapsulates the transition between reflection and experience, as well as the enactment and the mourning, of the terrible loss. In analyzing Winkler's translational choices, the article sheds light on Rübner's "self-translations," while calling attention to Winkler's own engagement with both languages in dealing with the horror of the Holocaust.